A study to determine the value of pre operative hyperbilirubinemia as a predictor of complicated appendicitis - Lal, Arun; Thomas, Thomas K.; Dayananda Babu, R.; Paul, Deepak (International Surgery Journal, 2020)
Background: Acute appendicitis is a common acute abdominal condition that all surgeons confront. The early detection of patients who could go in for complication is critical so that appropriate treatment can be initiated to reduce mortality. There is no pre-operative investigation which accurately point out the patients who are going to develop severe disease. Hence this prospective study was done to identify whether preoperative bilirubin level can predict the severity of the disease. Methods: The study was conducted in the Department of General Surgery, Sree Gokulam Medical College and Research Foundation, Venjaramoodu, Trivandrum on 100 consecutive patients who were clinically diagnosed as acute appendicitis. These patients were evaluated with Alvarado score. In addition, preoperative bilirubin level and liver enzymes were estimated. Ultrasound abdomen was done preoperatively routinely. After surgery histopathology was studied. The parameters which showed statistically significant results for predicting complications were analyzed. Results: In this prospective study on 100 consecutive patients, acute appendicitis was found more commonly in males, 57 (57%) cases than in females, 43 (43%) cases. Among the cases 56 were acute appendicitis, 13 perforated, 11 gangrenous and 20 suppurative appendicitis. In our study, there was significant correlation of preoperative hyperbilirubinemia with complications of appendicitis. Conclusions: Patients with appendicitis with elevated bilirubin levels have more chance for complications like perforation, gangrene and suppuration.